HUBUNGAN PENGETAHUAN TENTANG KOMPLIKASI DIABETES MELLITUS DENGAN PERILAKU DALAM MENCEGAH KOMPLIKASI PENYAKIT PADA PENDERITA DIABETES MELLITUS - Patimah, Siti; Utomo, Wasisto; Elita, Veny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Sugar level of Diabetes Mellitus patients needs to be controlled properly in order to prevent further complication. Knowledge and behavior of the patients in preventing complication is a means to help run the treatment of Diabetes Mellitus in their lifetime. This study aims to determine the relationship between knowledge of Diabetes Mellitus complication and behavior in preventing complication of disease of Diabetes Mellitus patients. The research design is descriptive correlation with Cross Sectional approach. The samples of the study were 30 respondents by using purposive sampling technique based on the inclusion criteria. A set of questionnaire that had been tested for its validity and reliability was used as the measuring tool. The analyses used were univariate analysis in order to know the frequency distribution and bivariate analysis using alternative test of Kolmogorov-Smirnov test. The result showed that among 30 respondents; 16 people (53.4%) had good knowledge, 7 people (23.3%) had adequate knowledge, 7 people (23.3%) had less knowledge, 17 people (56.7%) had good behavior, and 13 people (43.3%) had bad behavior. The statistical test resulted in p value 0.193 > alpha (0.05), so it can be concluded thatH0 failed to be rejected or n there iso relationship between knowledge of complication of diabetes mellitus and behavior in preventing complication of diabetes mellitus patients. It is suggested that nurses should be active in giving health education program related to preventing complication of Diabetes Mellitus.Keywords:Behavior, complication, diabetes mellitus, knowledge